2020
DOI: 10.1186/s12891-020-03583-w
|View full text |Cite
|
Sign up to set email alerts
|

Classifications of good versus poor outcome following knee arthroplasty should not be defined using arbitrary criteria

Abstract: A recently published paper by te Molder and colleagues in BMC Musculoskeletal Disorders confirmed prior reports indicating that definitions of good versus poor outcome cutoff scores for relevant knee arthroplasty outcomes including pain and function are heterogeneous and that this heterogeneity prevents generalizable inferences. In this Correspondence, we highlight an additional and, in our view, a more important problem with the substantial literature on this topic. There also is high homogeneity in that all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Our concerns are centered on the methods utilized to calculate MCIDs. We have made similar arguments in prior publications 7-10 and elaborate on our concerns in the present review. Herein, we present the limitations of MCIDs that, in our opinion, justify why they should not be routinely utilized by orthopaedic surgeons.…”
Section: Structure and Function Of The Minimal Clinically Important D...mentioning
confidence: 55%
“…Our concerns are centered on the methods utilized to calculate MCIDs. We have made similar arguments in prior publications 7-10 and elaborate on our concerns in the present review. Herein, we present the limitations of MCIDs that, in our opinion, justify why they should not be routinely utilized by orthopaedic surgeons.…”
Section: Structure and Function Of The Minimal Clinically Important D...mentioning
confidence: 55%
“…T he presence of multiple bodily pain sites in patients undergoing TKA is known to be a strong prognostic indicator of poor outcome 11,13,32 . Chronic widespread pain, a characteristic of nociplastic pain 33 , was relatively common in our TKA sample (43% at baseline) and likely results from maladaptive changes to the nervous system leading to heightened central nervous system pain sensitivity 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…One such methodology is the latent class analysis (LCA) used to differentiate good from poor outcome. Riddle et al [10] showed high discrimination between good and poor outcomes using the LCA methodology in a US-based total knee replacement cohort. They also have shown excellent reproducibility in a large total knee replacement cohort recruited in England [12].…”
Section: How Do We Get There?mentioning
confidence: 99%